Case Study of Hypertension in Pregnancy - Putu Aryani, Ni; Ricca Afrida, Baiq; Idyawati, Susilia (Journal of Fundus, 2021)
Hypertension in pregnancy can cause eclampsia, preterm birth, impaired fetal growth, respiratory syndrome, and fetal death. The aimed of this research was to provide midwifery care on pregnant women with hypertension in pregnancy. Type of this research was descriptive qualitative with case study approach, the instrument of data collection used in this research was interview, analysis obtained from case studies by making a narrative from the results of observations and analysis of midwifery care to documentation using SOAPIE method. The results of the research obtained that Mrs. “SU” aged 36 years G4P3A0 UK 23 weeks with hypertension in pregnancy, then an intervention was carried out according to the management of hypertension in pregnancy, one of which was taking 10 mg amlodipine for one month, blood pressure dropped from 150/100mmHg. Amlodipine oral 10 mg 3x1 day, to lower blood pressure which is safe for pregnant women. Based on the results of the research on the management of Hypertension in Pregnancy, after one month the mother's blood pressure was found to be 140/90 mmHg